Duodenal de-rotation as a determinant step for management of high jejunal atresia: Proximal duodenal plication after resection of dilated dysmotile segments - Seyed Abbas Banani; Hamidreza Foroutan; Mehdi Forooghi; Omid Azh; Ali Tadayyon (Global Pediatrics, 2023)
Background: Due to its distal mechanical obstruction, dilated duodenum is present in almost all patients with high jejunal atresia (HJA). If the former problem, which causes duodenal dysmotility, is not handled appropriately, traditional management of HJA alone is usually associated with feeding intolerance and prolonged hospitalization. In the present introduced technique, when added to classic surgical management of HJA, satisfactory results would be obtained. Methods: Newborns with HJA in the vicinity of the ligament of Treitz were managed, since May 2015 till November 2021, by this procedure in sequence as follows: duodenal de-rotation (DD); resection of the dilated and patulous proximal jejunum along with resection of the dilated third and fourth portions of the duodenum (D3 & D4). The dilated first and second portions of the duodenum (D1 & D2) were managed by one of the following options: anterolateral plication (ALP) or anterolateral resection (ALR) (manually or by stapler) preceded or followed by duodeno-jejunostomy respectively. Finally, appendectomy is done and the right colon is positioned at the left side of the abdomen. Results: Twelve patients were managed by this procedure, two of whom expired after the operation due to unrelated problems, thereby excluded from this series. In ten patients (2–4 days old babies, eight males, two females), ALP was done in four, while six others were managed by ALR (depending on the surgeon preferences, three by stapler, three by manual resection). All these patients had an uneventful recovery. The first feeding could be tolerated ranging from 4 to 6 days after the operation; on average one day earlier in ALP patients. Post-operative length of hospitalization was 6–13 days (on average, 7 and 9.3 days in ALP and ALR groups, respectively). Regardless of the type of operation in this series, there was no significant difference in final results. However, Hospital charge in patients managed by ALP with shorter hospital stays was less than those managed by ALR. During follow-up periods (9 months to 6.5 years; on average 35.2 months), the patients were asymptomatic. Conclusion: Dysmotility of dilated duodenum, which is the hallmark of HJA, if not handled properly, would cause prolonged hospitalization due to feeding intolerance. Thus, traditional management of this kind of atresia alone is not usually associated with acceptable results unless the limiting factors (inaccessible dilated D3 and D4 under the pancreas and superior mesenteric vessels) are overcome by DD after which the dilated segments of the duodenum and jejunum, now safely approachable, can be managed appropriately.